As interferências subjetivas do processo de aquisição de outra língua em mulheres em situação de cárcere - Lopes, Natalia Luiza Carneiro (2015)
The theme of this master's thesis took as its starting point the situation of some women who were on the English language acquisition process in prison, either through the school in the prison or by themselves. Some of them could thrive in the foreign language fluently, while others could not even make simple greetings in English, although they are studying that language. This language acquisition situation and prison brought us the intention of investigating subject effects of the unconscious on the individual inmate apprentice of second language, on the assumption that learning a foreign language is not without striking consequences for the subject. Here we do not intend to treat about modifications, when it comes to the possibility of employment, possibilities of changes to study in other countries or economic improvements that the new language can bring to the inmates in the future. This research anchors in the concepts of structural linguistics, here represented by Saussure and Jakobson and the freud-lacanians concepts directed to the question of language. Starting from the notion of the unconscious structured like a language, proposed by Lacan, the subject of significant effect, we try to guide our work in language acquisition theorists who seek articulation with psychoanalysis, as Claudia de Lemos, Charles Melman, Jean-Claude Milner, and others. Learning a foreign language is complex because it calls, at the same time, our relationship with knowledge, with the body and with ourselves while speaking subjects. In addition, as proposed Revuz (2002), it is a process that calls the bases of our psychic structure, and with them, the same time, the tool and the material of this structure, in other words, the mother language. Therefore, any attempt to learn another language is disturbing, questioning, modify what is inscribed in us with the words that first language. So, from the foundation of Revuz (2002),we investigate subject effects of the unconscious on the individual inmate apprentice of second language, which can be pointed in the discourse of inmates who are in the process of acquiring a foreign language, the traces of the loop particular that subjects have with the mother language, the interference of the English language acquisition process in that particular loop and the subjective effects of changes in this loop. To this end, we will try to understand the relationship of the participants in this study with the English language and mother language, what they think about it and we will try to get on what the English language transform them, if it transforms and for what way this occurs. As analysis material, we chose a semi-structured interview because we believe that this genre allows that the "I" takes the word and that each participant can enter the attempt to express elements that could point their relationship with the mother tongue and foreign language. For analysis purposes, we gave full attention to the speech of each participant. We seek throughout this speech, elements that could bring traces that capture, or not, of a foreign language. The results showed elements that can contribute, in principle, for studies that work with issues relating to language taking into account the findings of psychoanalysis, which causes considerable changes in conceptions about language and about the relationship between language and the human constitution. This contribution is interdisciplinary in a dialogue between fields of knowledge, and a level of consciousness of all those who participate effectively in the construction and reconstruction of human realities.